Surgical Aspects of a Lower Face, Mandible, and Tongue Allotransplantation - Cavadas, Pedro C.; Ibáñez, Javier; Thione, Alessandro (Journal of Reconstructive Microsurgery, 2012)
Face transplantation is a novel treatment for the reconstruction of massive facial defects. To date 13 cases have been performed. The technical aspects of a composite lower face transplantation including the tongue, floor of the mouth, and most of the mandible are detailed. The transplantation was performed in August 2009 in an HIV-positive, postoncologic patient. A preparatory surgery for nerve identification was performed. Facial composite tissue was procured after cardiac cessation. Revascularization was performed to the right subclavian artery with an internal shunt between the internal carotid arteries. At 16 months posttransplantation the patient is swallowing, without evidence of malignancy recurrence or HIV replication.
Keywords: face transplantation; tongue transplantation; malignancy; radionecrosis; HIV; vascularized composite allotransplantation